Risk and protective factors for symptoms of anxiety and depression in parents of children with autism spectrum disorder. (3rd May 2016) - Machado Junior, Samuel Bezerra; Celestino, Meline Ivone Oliveira; Serra, Juliane Penalva Costa; Caron, Jean; Pondé, Milena Pereira
Abstract: Objective : The severity of symptoms of anxiety and depression was evaluated in 102 parents of children with autism spectrum disorders (ASD) and correlated with the severity of their child's behavioral symptoms. Design : An observational, cross-sectional study. Methods : The Portuguese versions of the Hospital Anxiety and Depression Scale and the Aberrant Behavior Checklist were used to assess symptoms in the parents and in their children. Main outcomes and results : Depression was present in 26.7% of parents and anxiety in 33.7%. Severe behavioral symptoms in the child increased the likelihood of severe anxiety and depression symptoms in the parents by a factor of 35. If the child had severe behavioral symptoms and the father lived in the family home, the likelihood of severe symptoms of anxiety and depression in the parents was 95.2% lower. Conclusion : The presence of the father living in the family home acted as a buffer against parents' symptoms.